Communicative Purpose as Genre Determinant - Askehave, Inger (HERMES - Journal of Language and Communication in Business, 1999)
Through the years researchers and LSP teachers alike have used various parameters for classifying texts. This article sets out to discuss the notion of ‘communicative purpose’ as a means for classifying text. It points to some of the difficulties associated with the functional approaches to genre classification in general and the notion of “commu-nicative purpose” in particular.